Influence of a full body compression suit on trunk control during cutting maneuvers - Mornieux, G.; weltin, E.; Pauls, M.; Rott, F.; Gollhofer, A. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to evaluate the influence of a full body compression suit on trunk control and knee joint moments during cutting maneuvers. Female athletes performed unanticipated cuttings with and without the tested apparel, while 3D kinematics and ground reaction forces were measured. Higher trunk lateral flexion was measured while wearing the compression suit (p < 0.001), whereas knee joint moments were not significantly different between the two conditions. It seems that participants relied on the compression suit to support their trunk, but as the apparel failed to limit the trunk range of motion, subjects had a higher trunk lateral flexion. However this trunk position was not associated with increased knee joint loading during cutting maneuvers.